Ethnography in education - Mills, David, 1969-; Morton, Missy; Sage eBooks (Los Angeles : SAGE, 2013)
The title will introduce you to ethnographic 'classics', the best existing textbooks, and debates about new approaches and innovations. With extended examples of ethnographic analysis by both established scholars and research students, the authors aim to help you cultivate an 'ethnographic imagination' in your own research and writing.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Educational anthropology -- Research; Electronic books